SAT0214 Comparison of Response to Tocilizumab Between Biologic-Naïve Patients and Non-Responder to TNF Inhibitor Failure in Rheumatoid Arthritis: A Retrospective Study Using the Y-Curd Registry. (9th June 2015) - Kunishita, Y.; Yoshimi, R.; Takeno, M.; Toyota, Y.; Sugiyama, Y.; Tsuchida, N.; Kishimoto, D.; Kamiyama, R.; Minegishi, K.; Hama, M.; Kirino, Y.; Asami, Y.; et al.
Abstract : Background: In the update of EULAR recommendations for management of rheumatoid arthritis (RA) in 2013, both TNF inhibitor (TNFi) and non-TNFi biologics (BIOs) are listed as a first biologics. A number of studies have shown that the therapeutic response to a BIOs is unfavorable in patients who failed to respond to previous BIOs compared with BIO-naïve patients. Little data are available to compare the response of tocilizumab (TCZ) as the first BIO with that as the second BIO, because TCZ had been recognized as the second line BIO until the 2013 EULAR recommendations. Objectives: To compare clinical responses of TCZ between BIO-naïve patients and non-responders to the first TNFi in RA. Methods: Patients with RA, who were registered in Y-CURD, the integrated database of patients at our department and its affiliated hospitals, and treated with TCZ as the first BIO (BIO-naïve group) and the second BIO after TNFi (infliximab, etanercept and adalimumab) failure (TNFi failure group) along with methotrexate were included in the study. We compared the clinical efficacy of TCZ as the first and second BIO by assessing tender joint count (TJC), swollen joint count (SJC), patient global assessment (PGA), and DAS28-ESR at 12 months after starting TCZ. Results: Among 40 patients recruited, 18 and 22 belonged to the BIO-naïve and TNFi failure groups, respectively. There was no significant difference in patient demographics including age (50.1±3.5 vs 52.2±3.6 yr), disease duration (9.1±3.5 vs 8.1±3.3 yr), and ACPA positivity (71.4% vs 81.8%) and all baseline clinical parameters, including TJC (7.7±1.3 vs 7.7±1.3), SJC (7.2±1.3 vs 6.0±1.1), PGA (50.2±5.4 vs 60.1±5.1 mm), and DAS28-ESR (5.45±0.31 vs 5.75±0.29), between the two groups. Although all these parameters were significantly reduced during the first 3 months after starting TCZ in the both groups, the levels of PGA and DAS28-ESR were significantly lower in the BIO-naïve group than the TNFi failure group (13.4±4.3 vs 31.0±6.6 mm, respectively, p =0.045, and 2.06±0.46 vs 3.20±0.30, respectively, p =0.041). Clinical remission rate based on DAS28-ESR was significantly higher in BIO-naïve group than in the TNFi failure group at 3 months (72.7% vs 26.7%, p =0.045), while there was no significant difference in remission rate from 6 to 12 months after starting TCZ between the two groups. Conclusions: Our data showed that TCZ acted more immediately in BIO-naïve RA patients as compared to non-responder to TNFi, whereas the long-term effectiveness of TCZ was equivalent between the two groups. TCZ may have a unique feature characterized by the efficacy irrelevant to the history of TNFi use. Disclosure of Interest: None declared